Perform a lecture! a project in six parts at different sites in Berlin - Blumenstein, Ellen; Geuß, Fiona (Argobooks, 2011)
Perform a Lecture! is a project in six parts that seeks to explore the genre of ‘lecture performance’ both practically and discursively. Developed in the 1960s as a subgenre of performance, lecture performances have been present in contemporary art for years. Perform a Lecture! brings together performances by internationally renowned and emerging artists, and approaches the genre, its history and recent developments in a series of conversations between art historians, curators, philosophers, artists and the audience. The presentations are organized in collaboration with various institutions in Berlin.
Umschlagtitel
Keywords: Lecture Performance; Aufsatzsammlung; Künstlerbuch